2019
DOI: 10.1016/j.resinv.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength measurement in patients with chronic obstructive pulmonary disease: Possible predictor of exercise capacity

Abstract: Background: Impaired exercise capacity is one of the most important prognostic factors for patients with chronic obstructive pulmonary disease (COPD). The 6-min walk test (6MWT) is a widely used method for assessing exercise capacity in patients with COPD. However, the 6MWT requires considerable effort from patients. Therefore, a less physically demanding, but also noninvasive, method is warranted. The objective of this study was to determine the predictors of the 6MWT distance (6MWD) in patients with COPD. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Another important finding of this study was the correlation of handgrip strength with 6MWT, Nesfatin-1 and Ghrelin levels, and inverse correlation with CAT score positivity and mMRC score. Similar with our results Kyomoto et al (20) reported that carbon monoxide diffusing capacity of the lungs and handgrip strength were strongly correlated with 6MWT in their study on 133 patients with COPD. In previous literature, decreased ghrelin levels were associated with the nutritional status of the COPD patients and ghrelin has been suggested for the treatment of COPD patients (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…Another important finding of this study was the correlation of handgrip strength with 6MWT, Nesfatin-1 and Ghrelin levels, and inverse correlation with CAT score positivity and mMRC score. Similar with our results Kyomoto et al (20) reported that carbon monoxide diffusing capacity of the lungs and handgrip strength were strongly correlated with 6MWT in their study on 133 patients with COPD. In previous literature, decreased ghrelin levels were associated with the nutritional status of the COPD patients and ghrelin has been suggested for the treatment of COPD patients (21)(22)(23).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is not surprising that the evaluation of muscle strength required for COPD management can be performed with HGS. In fact, there was one recent report showing significant correlation between 6MWT and HGS in COPD [ 8 ]. Although HGS has not yet been used in general medical care for COPD, because of its simplicity—it can be measured simply by grasping the grip-strength meter—it may become a useful evaluation method in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, HGS is associated with the antioxidant indicators serum club-cell protein 16 (CC16) and total sialic acid, which also predict forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) [ 7 ]. HGS is also associated with the distance walked in the 6MWT, frequency of COPD exacerbation, and inspiratory flow rate [ 8 10 ], but evidences in this area are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as recent and numerous studies showed, the handgrip test turns out to be a predictor of various diseases (Mgbemena, 2019;Kyomoto, 2019).…”
Section: Discussionmentioning
confidence: 95%